Transcription Factor SmWRKY1 Positively Promotes the Biosynthesis of Tanshinones in Salvia miltiorrhiza - Cao, Wenzhi; Wang, Yao; Shi, Min; Hao, Xiaolong; Zhao, Weiwei; Wang, Yu; Ren, Jie; Kai, Guoyin (Frontiers in Plant Science, 2018)
Tanshinones, one group of bioactive diterpenes, were widely used in the treatment of cardiovascular diseases. WRKYs play important roles in plant metabolism, but their regulation mechanism in S. miltiorrhiza remains elusive. In this study, one WRKY transcription factor SmWRKY1 was isolated and characterized from S. miltiorrhiza. Multiple sequence alignment and phylogenetic tree analysis showed SmWRKY1 shared high homology with other plant WRKYs such as CrWRKY1. SmWRKY1 were predominantly expressed in leaves and stems, and was responsive to salicylic acid (SA), methyl jasmonate (MeJA) and nitric oxide (NO) treatment. Subcellular localization analysis found that SmWRKY1 was localized in the nucleus. Over-expression of SmWRKY1 significantly elevated the transcripts of genes involved in MEP pathway especially 1-deoxy-D-xylulose 5-phosphate synthase (SmDXS) and 1-deoxy-D-xylulose 5-phosphate reductoisomerase (SmDXR), resulted in over 6 folds increase in tanshinones production in transgenic lines (up to 13.731mg/g dry weight (DW)) compared with the control lines. Dual-luciferase (Dual-LUC) assay showed that SmWRKY1 can positively regulate SmDXR expression by binding to its promoter. Our work revealed that SmWRKY1 participated in the regulation of tanshinones biosynthesis and acted as a positive regulator through activating SmDXR in the MEP pathway, thus discloses a new insight to further excavate the regulation mechanism of tanshinones biosynthesis.